LETM1 haploinsufficiency causes mitochondrial defects in cells from humans with Wolf-Hirschhorn syndrome: implications for dissecting the underlying pathomechanisms in this condition - Lesley Hart; Anita Rauch; Antony M. Carr; Joris R. Vermeesch; Mark O'Driscoll (The Company of Biologists, 2014)
Wolf-Hirschhorn syndrome (WHS) represents an archetypical example of a contiguous gene deletion disorder - a condition comprising a complex set of developmental phenotypes with a multigenic origin. Epileptic seizures, intellectual disability, growth restriction, motor delay and hypotonia are major co-morbidities in WHS. Haploinsufficiency of LETM1, which encodes a mitochondrial inner-membrane protein functioning in ion transport, has been proposed as an underlying pathomechanism, principally for seizures but also for other core features of WHS, including growth and motor delay. Growing evidence derived from several model organisms suggests that reduced LETM1 expression is associated with some element of mitochondrial dysfunction. Surprisingly, LETM1-dependent mitochondrial functional deficits have not previously been described in cells from individuals with WHS. Here, using a unique panel of WHS-patient-derived cell lines with deletions of differing sizes, incorporating LETM1 or not, we show, for the first time, that LETM1 expression is reduced in mitochondria isolated from WHS-patient cells. Furthermore, we show that this is associated with distinct mitochondrial phenotypes, including altered intracellular [Ca2+] levels, dysfunctional mitochondrial transition-pore opening, hyperpolarization and superoxide leakage from resting mitochondria. Interestingly, we find that these phenotypes segregate with seizures in our WHS cohort. Our findings identify novel cellular phenotypes in WHS attributable to a 50% reduction in LETM1 expression level; these phenotypes could underlie and/or contribute to some of the core clinical features of this condition.